Likert scale versus the visual analogue scale in evaluating dentofacial aesthetics: a systematic review - Marzuki Hanis Nabilah; Zahirah Izzah; Lau May Nak; Kuppusamy Elavarasi; Mustapha Nik Mukhriz Nik; Ashari Asma (Sciendo, 2024)
Numerous studies rating dentofacial aesthetics have been conducted by using the Likert Scale or the Visual Analogue Scale (VAS). The Likert Scale is an assessment tool consisting of items that require respondents to rank a query using graded declarative statements. Alternatively, the VAS is a tool that requires the respondents to place a mark along a horizontal line to rate a particular item.